2016
DOI: 10.1177/0003319716674623
|View full text |Cite
|
Sign up to set email alerts
|

Preprocedural High-Sensitivity C-Reactive Protein Predicts Contrast-Induced Nephropathy and Long-Term Outcome After Coronary Angiography

Abstract: We investigated whether high-sensitivity C-reactive protein (hsCRP) levels were associated with contrast-induced nephropathy (CIN) and long-term mortality after coronary angiography (CAG). Patients (N = 2133) undergoing CAG with preprocedural hsCRP were consecutively enrolled. High-sensitivity C-reactive protein was measured before angiography. Median follow-up was 2.3 years. The overall incidence of CIN was 2.77% (59 of 2133). There was a positive trend of hsCRP quartiles (Q) with rates of CIN: 0.9% for Q1 (<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…As shown in Table 3, Univariate logistic regression found that diabetes mellitus, Scr > 124 μmol/L and UAPN> 12.24 ng/ml were associated with CIN (all P < 0.05). The contrast volume > 300 ml and Hs-CRP as common risk factor used in clinical practice were also included in the multivariate logistic regression analysis [16, 17]. Multivariate analysis indicated that UAPN> 12.24um/ml (OR, 5.071; 95% CI, 1.711–15.028; P < 0.01) and Scr > 124 μmol/L (OR, 4.210; 95% CI, 1.297–13.669; P < 0.01) remained significant predictors for developing CIN in patients undergoing elective PCI (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 3, Univariate logistic regression found that diabetes mellitus, Scr > 124 μmol/L and UAPN> 12.24 ng/ml were associated with CIN (all P < 0.05). The contrast volume > 300 ml and Hs-CRP as common risk factor used in clinical practice were also included in the multivariate logistic regression analysis [16, 17]. Multivariate analysis indicated that UAPN> 12.24um/ml (OR, 5.071; 95% CI, 1.711–15.028; P < 0.01) and Scr > 124 μmol/L (OR, 4.210; 95% CI, 1.297–13.669; P < 0.01) remained significant predictors for developing CIN in patients undergoing elective PCI (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…33 C-reactive protein was found to be an independent predictor of CIN after coronary angiography. 34 In recent studies, PLR and NLR emerged as independent predictors of CIN in patients with STEMI after primary PCI. 18,35 In our study, we showed that PLR is associated with an increased risk of CIN.…”
Section: Discussionmentioning
confidence: 99%
“…C-reactive protein and IL-6 are markers of inflammatory response and are also closely related to CIN. [25][26][27] In this study, whether in the alprostadil group or in the control group, CRP and IL-6 levels were higher after operation at 48 and72 hours compared with baseline (P < .05), indicating that the use of contrast agent had an inflammatory reaction. In the alprostadil group after operation at 48 and 72 hours, CRP and IL-6 levels were lower compared with the control group (P < .05), which indicated that the treatment with alprostadil had an antiinflammatory effect.…”
Section: Discussionmentioning
confidence: 53%